The Musical Heritage of Water Puppet Performances in Hanoi, Socialist Republic of Vietnam - Sarisa Prateepchuang,; Supunnee Leauboonshoo,; Truong Ngoc Thang, (Wacana Seni Journal of Arts Discourse, 2016)
R?i n??c (water puppetry) is a national art of Vietnam that represents the traditions, folklore, beliefs and lifestyle of the local people. This qualitative research is conducted in the context of Hanoi, Socialist Republic of Vietnam. The research objectives are to understand the history, status and role of the water puppet show, its music and inheritance. This article shows that the water puppet shows are widely found in many villages and provinces in the alluvial plains of the Red River Delta. The important elements of the water puppet show are the puppets, music, puppeteers, mechanisms and manipulation methods, theater and story. The music in water puppet shows was formerly produced by percussion instruments, such as Tr?ng Cái (drum), Chúm Cho? (cymbals) and M? (wooden percussion instrument). Presently, many more musical instruments have been added to create more melodies. The sound of music in the water puppet show is from the folk song called Chèo, which is a short melodic verse played repeatedly. The melodic verse style is matched with the dancing posture of the puppets. The music of the water puppet show has been adapted to the changing social and western influences through conservation, rehabilitation, musical application and new generation compositions.